Secondary Worsening Following DYT1 Dystonia Deep Brain Stimulation: A Multi-country Cohort - Tsuboi, Takashi; Cif, Laura; Coubes, Philippe; Ostrem, Jill L.; Romero, Danilo A.; Miyagi, Yasushi; Lozano, Andres M.; De Vloo, Philippe; Haq, Ihtsham; Meng, Fangang; Sharma, Nutan; Ozelius, Laurie J.; et al. (Frontiers in Human Neuroscience, 2020)
Objective: To reveal clinical characteristics of suboptimal responses to deep brain stimulation (DBS) in a multi-country DYT1 dystonia cohort. Methods: In this multi-country multi-center retrospective study, we analyzed the clinical data of DYT1 patients who experienced suboptimal responses to DBS defined as < 30% improvement in dystonia scales at the last follow-up compared with baseline. We used a literature-driven historical cohort of 112 DYT1 patients for comparison. Results: Approximately 8% of our study cohort (11 out of 132) experienced suboptimal responses to DBS. Compared with the historical cohort, the multi-country cohort with suboptimal responses had significantly younger age at onset (mean, 7.0 vs 8.4 years; p = .025) and younger age at DBS (mean, 12.0 vs. 18.6 years; p = .019). Additionally, cranial involvement was more common in the multi-country cohort (before DBS, 64% vs. 45%, p = 0.074; before or after DBS, 91% vs. 47%, p = 0.001). Mean motor improvement at the last follow-up from baseline were 0% and 66% for the multi-country and historical cohorts, respectively. All 11 patients of the multi-country cohort had generalization of dystonia within 2.5 years after disease onset. All patients experienced dystonia improvement of > 30% postoperatively; however, secondary worsening of dystonia commenced between 6 months and 3 years following DBS. The improvement at the last follow-up was less than 30% despite optimally-placed leads, a trial of multiple programming settings, and additional DBS surgeries in all patients. The on-/off-stimulation comparison at the long-term follow-up demonstrated beneficial effects of DBS despite missing the threshold of 30% improvement over baseline. Conclusion: Approximately 8% of patients represent a more aggressive phenotype of DYT1 dystonia characterized by younger age at onset, faster disease progression, and cranial involvement, which seems to be associated with long-term suboptimal responses to DBS (e.g., secondary worsening). This information could be useful for both clinicians and patients in clinical decision making and patient counseling before and following DBS implantations. Patients with this phenotype may have different neuroplasticity, neurogenetics, or possibly distinct neurophysiology.